A General and Convenient Preparation of [Bis(trifluoroacetoxy)iodo]perfluoroalkanes and [Bis(trifluoroacetoxy)iodo]arenes by Oxidation of Organic Iodides Using Oxone and Trifluoroacetic Acid; The Journal of Organic Chemistry; Vol. 75, iss. 6 - Zagulyaeva A. A. (2010, 2010)
Title screen